(untitled) (diségno, 2023)
In recent years, architecture has undergone a significant transformation with the introduction of digital tools and techniques. Three prominent techniques in this context are drawing, scripting, and prompting, offering architects novel approaches to the design process. Drawing remains a vital tool for idea exploration and design development. Conversely, scripting and prompting are digital methods that enable a more algorithmic and data-driven design approach. This paper explores the intersection of these techniques and their potential to enhance the design process. By using them together, architects can foster creativity, efficiency, and innovation while allowing more time for conceptual development. The paper analyzes the framework posed by these techniques, including the impact of new digital technologies like generative and algorithmic design, and artificial intelligence. The potential of scripting to automate graphic tasks, such as parametric design and generative drawing, is addressed. Furthermore, the paper delves into the new frontier of prompting and its application in architectural graphics, outlining the competencies architects need to effectively utilize this technology. In conclusion, this paper critically evaluates the current state of architectural graphics, exploring the fusion of traditional and digital methods, and how new technologies can transform the design process.